The first BCR gene intron contains breakpoints in Philadelphia chromosome positive leukemia. - Heisterkamp, N (1988)
The hallmark of chronic myelogenous leukemia (CML) is a translocation between chromosomes 9 and 22 - the Philadelphia (Ph') translocation. The translocation is also found in acute lymphocytic leukemia (ALL) albeit in a lower percentage of patients. The breakpoint on chromosome 22 is located within the BCR gene: in CML, breakpoints are clustered within 5.8 kb of DNA, the major breakpoint cluster region (Mbcr). In ALL, breakpoints have been reported within the Mbcr but also in more 5' regions encompassing the BCR gene. To characterize the latter breakpoints, we have molecularly cloned and mapped the entire gene, which encompasses approximately 130 kb of DNA. Mbcr negative, Ph'-positive ALL breakpoints were not distributed at random within the gene but rather were found exclusively within the 3' half of the first BCR gene intron. In contrast to the Mbcr, which is limited to a region of 5.8 kb, this part of the intron has a size of 35 kb. Translocation breakpoints in this region appear to be specific for ALL, since it was not rearranged in clinically well-defined CML specimens nor in any other tumor DNA samples examined.